A Domain-Sensitive Threshold Derivation Method - Mori, Allan; Vale, Gustavo; Cirilo, Elder; Figueiredo, Eduardo (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2019)
Software metrics provide means to quantify several attributes of information systems. The effective measurement is dependent of appropriate metric thresholds as they allow characterizing the quality of information systems. Several methods have been proposed to derive metric thresholds, however, previous methods do not take characteristics of software domains into account, such as the difference between size and complexity of systems from different domains. Instead, they rely on (generic) thresholds that are derived from heterogeneous systems. Although derivation of reliable thresholds has long been a concern, we also lack empirical evidence about threshold variation across distinct mobile software domains. This paper proposes a domain-sensitive method to derive thresholds that respects metric statistics and is based on benchmarks of systems from the same domain. To evaluate our method, we manually mined one hundred mobile systems from Fossdroid, measured them using a set of seven well-known metrics, derived thresholds, and validated them through qualitative and quantitative analyses. As a result, we observed that our method gathered more reliable thresholds considering software domain as a factor when building benchmarks for threshold derivation.